The Fall of Artemis: The Secret Recipe of St. Paul's Slow Disciple-Making in Ancient Ephesus - Christianto, Victor (Jurnal Teologi Amreta (ISSN: 2599-3100), 2025)
The present article explores St. Paul's approximately three-year ministry in Ephesus as a profound case study in transformative disciple-making, which we suggest a term : “slow disciple-making” method. Focusing on Acts chapter 19, it argues that Paul's remarkable breakthrough in undermining the worship of Artemis, culminating in the uprising led by Demetrius, stemmed from a deliberate "slow disciple-making" approach. This method encompassed intensive coaching, deep Bible engagement, and a process of re-conscientization, which systematically challenged and transformed the prevailing pagan worldview. The paper further connects Paul's exemplary work to the subsequent dramatic destruction of idols, including the statue of Artemis, as narrated in the apocryphal Acts of John (chapters 38-45), portraying it as a culmination of the spiritual groundwork laid by Paul. This article contends that this long-term disciple-making was a blueprint that St Paul also intended to replicate in Rome and was a methodology profoundly exemplified by Jesus Christ Himself.